Comparing observations of closely located JUICE and STEREO-A spacecraft during the widespread 13 May 2024 solar energetic particle event - Rodríguez-García, L.; Palmerio, E.; Pinto, M.; Dresing, N.; Cohen, C. M. S.; Gómez-Herrero, R.; Gieseler, J.; Santos, F.; Espinosa Lara, F.; Cernuda, I.; Mewes, M.; Vallat, C.; et al. (EDP SCIENCES S A, 2026)
Context. Following its launch in April 2023, JUICE is now in its cruise phase to Jupiter, where it is scheduled to arrive in July 2031. JUICE carries a radiation monitor, namely the RADiation hard Electron Monitor (RADEM) to measure protons, electrons, and ions, detecting particles coming mainly from the anti-Sunwards direction. On 13 May 2024, a large solar energetic particle (SEP) event took place in association with an eruption close to the western limb of the Sun, as seen from Earth. Providentially, at that time, JUICE was located very close to STEREO-A, separated by only 0.13 au in radial distance, 0.3 degrees in latitude, and 1.6 degrees in longitude.
Aims. Our main aims are to characterise the observations within the interplanetary (IP) context whereby SEPs propagated to near-Earth, JUICE, and STEREO-A observers, while performing a first comparison of energetic particle instruments on board JUICE and STEREO-A spacecraft.
Methods. We analysed the IP context using in situ measurements and studied the proton anisotropies measured by near-Earth spacecraft and STEREO-A. We focussed on an isotropic period during the decay phase of the SEP event to compute the proton energy spectrum. We fit the STEREO-A spectrum and compared it to the one measured by SOHO and JUICE.
Results. We find the proton spectral indices measured by JUICE, SOHO, and STEREO-A to be similar. The proton fluxes measured by RADEM are in agreement with those from STEREO-A, with a deviation of less than 25%.
Conclusions. The RADEM instrument aboard JUICE is a valuable tool for measuring SEP events in the heliosphere, providing an excellent opportunity to study and characterise the energetic particle environment in the solar wind between 0.65 and 5.2 au. The intercalibration factors between the fluxes measured by STEREO-A and JUICE at the effective energies of 6.9 MeV, 13.3 MeV, 21.6 MeV, and 31.2 MeV are 1.02, 1.23, 1.12, and 0.95, respectively. We note that these intercalibration factors are valid only until 2024 July 10, when the configuration of the RADEM instrument was changed.